Corpo-escrita de mulheres: violência, memória e trauma em Conceição Evaristo e Marcela Serrano - Bruna Stéphane Oliveira Mendes da Silva (2020)
The purpose of this article is to analyze the marks of violence and its rememoration present in accounts produced by female characters featured in several short stories from the books Insubmissas lágrimas de mulheres (2016), by Conceição Evaristo, and Diez mujeres (2011), by Chilean writer Marcela Serrano, taking into account the concepts of autofiction, under the perspective of authors Philippe Lejeune, Serge Doubrovsky, Philippe Vilain, Philippe Gasparini, Vicent Colonna and Eurídice Figueiredo; of memory and trauma, employing concepts by Aleida Assmann, Jeanne-Marie Gagnebin and Márcio Seligmann-Silva; and of violence, from the viewpoint of Jaime Ginzburg, Karl Erik Schøllhammer, Hanna Arendt and Heleieth Saffioti. In both pieces were identified female languages emancipated from the universal masculine voice, willing to expose and resignify problematic realities, as well as the overlapping between violence and power relations, adopting the body as its main element. There can also be observed important intersections between gender, race and social class, which shape the writing that translates itself into singular characters.